2009
DOI: 10.1111/j.1365-2648.2009.05078.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life in Taiwanese survivors of childhood cancer

Abstract: Interventions and assessment of their efficacy are necessary to help survivors capitalize on their strengths, to decrease their individual risks and to promote resilience promote self-control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 28 publications
0
49
1
4
Order By: Relevance
“…Survivors were fearful of their cancer returning, 27,31 developing a secondary cancer, passing cancer to their children, infertility, 31 experiencing disability, and being unable to perform role expectations. 27 Survivors in Casillas et al's study experienced anxiety when attending long-term follow-up visits because they feared receiving news of cancer recurrence. 36 In a study by Cantrell and Conte, survivors expressed a desire to plan for and dream about their future, but prevailing feelings of uncertainty prevented them from doing so.…”
Section: 34mentioning
confidence: 99%
See 4 more Smart Citations
“…Survivors were fearful of their cancer returning, 27,31 developing a secondary cancer, passing cancer to their children, infertility, 31 experiencing disability, and being unable to perform role expectations. 27 Survivors in Casillas et al's study experienced anxiety when attending long-term follow-up visits because they feared receiving news of cancer recurrence. 36 In a study by Cantrell and Conte, survivors expressed a desire to plan for and dream about their future, but prevailing feelings of uncertainty prevented them from doing so.…”
Section: 34mentioning
confidence: 99%
“…The majority of the studies included both males and females. [24][25][26][27][28][29][30][31][32][33][34] Three studies did not indicate the gender distribution, [35][36][37] and the remaining two studies reported the inclusion of either all females 38 or all males. 39 The age of participants included in the studies ranged from 13 to 38 years old at the time of interview.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations